Advancing Chimeric Antigen Receptor T-Cell Therapy for Acute Myeloid Leukemia: Current Limitations and Emerging Strategies - Daniela Damiani; Mario Tiribelli (Pharmaceuticals)
Chimeric antigen receptor (CAR) T-cell therapy represents one of the most impressive advances in anticancer therapy of the last decade. While CAR T-cells are gaining ground in various B cell malignancies, their use in acute myeloid leukemia (AML) remains limited, and no CAR-T product has yet received approval for AML. The main limitation of CAR-T therapy in AML is the lack of specific antigens that are expressed in leukemic cells but not in their healthy counterparts, such as hematopoietic stem cells (HSCs), as their targeting would result in an on-target/off-tumor toxicity. Moreover, the heterogeneity of AML and the tendency of blasts to modify surface antigens’ expression in the course of the disease make identification of suitable targets even more challenging. Lastly, AML’s immunosuppressive microenvironment dampens CAR-T therapeutic activities. In this review, we focus on the actual pitfalls of CAR T-cell therapy in AML, and we discuss promising approaches to overcome them.